Fracture Toughness of Fibrous Concrete Incorporated with Treated Recycled Aggregates - Hano, Muna M. A.; Hano, Salwa M. A.; Ahmed, Sofyan Y. (Civil Engineering Journal, 2025)
This paper examines the effect of recycled concrete aggregate (RCA) on the behavior of concrete, particularly when combined with different fiber mesh and treatment techniques. Recycled concrete aggregate was treated using two treatment methods. Method 1 used a mix of cement, silica fume, and water, while Method 2 combined cement, silica fume, water, sand, and superplasticizer. Two types of fiber, glass and polypropylene (plastic) fiber mesh, were placed across the expected crack path to study their effect on crack resistance. A total of 24 prisms were cast and tested. Tests measured slump, absorption, unit weight, compressive strength, and fracture toughness. The findings indicate that using recycled concrete aggregate decreases strength and workability compared to normal aggregate. Treated recycled aggregate enhanced the strength, especially in Method 2, which provided compressive strength even higher than normal aggregate. However, fracture toughness decreased due to the sudden formation of cracks. Interestingly, concrete made with untreated recycled concrete aggregate and glass fiber exhibited better crack resistance and fracture toughness. This study compares RCA treated using two different methods and reinforced with two types of fiber mesh, showing that minor changes in the mix design can enhance the behavior of concrete made with RAC.